2021
DOI: 10.37190/ppmp/143580
|View full text |Cite
|
Sign up to set email alerts
|

LCD panels bioleaching with pure and mixed culture of Acidithiobacillus

Abstract: The influence of pure and mixed culture of A. ferrooxidans and A. tiooxidans as well as different pulp density (1 and 2%) of LCD panels on the In and Sn bioleaching efficiency was investigated. Pulp density is one of the factors affecting the metals extraction efficiency during biological leaching. It has been shown that lower pulp density results in higher indium and tin dissolution. The A. ferrooxidans bioleaching system showed better metal extraction results than A. thiooxidans, especially for tin, indicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 19 publications
0
5
0
2
Order By: Relevance
“…The results pointed out a higher level of efficiency in 9K medium with 55.6% leaching rate for Indium and more than 90% efficiency for Tin. The study also observed the role played by the presence of ferrous/ferric iron in leaching out tin from LCD and a simultaneous reduction of Tin content with increment in the recovery rate of Indium (Willner et al, 2018). A comparative study on leaching out metals from MPPCB and computer PCB using chemical leaching process and bio-hydrometallurgical process proves that the latter could be more efficient, ecologically sound and cost-efficient than the former (Shah et al, 2014).…”
Section: Microbial Leaching From Mobile Phonesmentioning
confidence: 79%
See 1 more Smart Citation
“…The results pointed out a higher level of efficiency in 9K medium with 55.6% leaching rate for Indium and more than 90% efficiency for Tin. The study also observed the role played by the presence of ferrous/ferric iron in leaching out tin from LCD and a simultaneous reduction of Tin content with increment in the recovery rate of Indium (Willner et al, 2018). A comparative study on leaching out metals from MPPCB and computer PCB using chemical leaching process and bio-hydrometallurgical process proves that the latter could be more efficient, ecologically sound and cost-efficient than the former (Shah et al, 2014).…”
Section: Microbial Leaching From Mobile Phonesmentioning
confidence: 79%
“…The results pointed out a higher level of efficiency in 9K medium with 55.6% leaching rate for Indium and more than 90% efficiency for Tin. The study also observed the role played by the presence of ferrous/ferric iron in leaching out tin from LCD and a simultaneous reduction of Tin content with increment in the recovery rate of Indium (Willner et al, 2018).…”
Section: Microbial Leaching From Mobile Phonesmentioning
confidence: 84%
“…It should also be noted here that the content of precious metals (in different electronic devices <0.5%) in PCBs is 10 times higher than a typical rich ore. Thus, the content of individual metals in PCBs determines the value of electronic scrap as a source of these materials [26].…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, the ferric ions further oxidize target insoluble metals, converting them into soluble metals (Sethurajan et al, 2018). Furthermore, Willner et al (2022) demonstrated that mixed bacteria of A. ferrooxidans and A. thiooxidans inoculated with iron and sulfur medium could achieve a high leaching yield of both indium (94.7%) and tin (98.2%). Aspergillus niger fermentation broth has also been explored for indium recovery from waste LCDs through an indirect bioleaching-based process, and indium bioleaching exhibited a significant achievement with a 100% yield of indium attained within a short time (1.5 h at 70 °C) (Cui et al, 2021).…”
Section: Indium Bioleachingmentioning
confidence: 99%